Gait and Functional Mobility in Multiple Sclerosis: Immediate Effects of Transcranial Direct Current Stimulation (tDCS) Paired With Aerobic Exercise - Pilloni, Giuseppina; Choi, Claire; Coghe, Giancarlo; Cocco, Eleonora; Krupp, Lauren B.; Pau, Massimiliano; Charvet, Leigh E. (Frontiers in Neurology, 2020)
Walking impairments are a debilitating feature of multiple sclerosis (MS) because of the direct interference with daily activity. The management of motor symptoms in those with MS remains a therapeutic challenge. Transcranial direct current stimulation (tDCS) is a type of non-invasive brain stimulation that is emerging as a promising rehabilitative tool but requires further characterization to determine its optimal therapeutic use. In this randomized, sham-controlled proof-of-concept study, we tested the immediate effects of a single tDCS session on walking and functional mobility in those with MS. Seventeen participants with MS completed one 20-min session of aerobic exercise, randomly assigned to be paired with either active (2.5 mA, n = 9) or sham (n = 8) tDCS over the primary motor cortex (M1). The groups (active vs. sham) were matched according to gender (50% vs. 60% F), age (52.1 ± 12.85 vs. 54.2 ± 8.5 years), and level of neurological disability (median Expanded Disability Status Scale score 5.5 vs. 5). Gait speed on the 10-m walk test and the Timed Up and Go (TUG) time were measured by a wearable inertial sensor immediately before and following the 20-min session, with changes compared between conditions and time. There were no significant differences in gait speed or TUG time changes following the session in the full sample or between the active vs. sham groups. These findings suggest that a single session of anodal tDCS over M1 is not sufficient to affect walking and functional mobility in those with MS. Instead, behavioral motor response of tDCS is likely to be cumulative, and the effects of multiple tDCS sessions require further study. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT03658668.